32.7k views
2 votes
Find the sum 6y square root a + 7y square root a

User YSY
by
4.9k points

2 Answers

5 votes
13y square root a is the correct answer. This can be acheived by combining like terms.
User Peter Smit
by
5.1k points
3 votes

Answer: The required sum is
13y\sqrt a.

Step-by-step explanation: We are given to find the sum of the following two radical expressions:


E_1=6y√(a),\\\\E_2=7y√(a).

Since both the expressions involve the same radical term, so we can simply take the radical term common and add the rest of the terms to get the result.

The summation is as follows:


S\\\\=E_1+E_2\\\\=6y√(a)+7y√(a)\\\\=(6y+7y)√(a)\\\\=13y√(a).

Thus, the required sum is
13y\sqrt a.

User Torinthiel
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.